Social-Ecological Processes and Impacts Affect Individual and Social Well-Being in a Rural Western U.S. Landscape - Bentley Brymer, Amanda L.; Toledo, David; Spiegal, Sheri; Pierson, Fred; Clark, Patrick E.; Wulfhorst, J. D. (Frontiers in Sustainable Food Systems, 2020)
To achieve agroecosystem conservation strategies while balancing the needs of people who live and work across rural landscapes, it is critical to understand what people need to improve and sustain their quality of life and well-being. Research that is designed to connect social-ecological dynamics, landscape change, and human impacts to human well-being and ecosystem health is well-suited to inform land management strategies and decision-making for agricultural production policies. We asked livestock producers, public land and resource managers, recreation users, conservationists, and wilderness advocates who live and work among rural communities in southwestern Idaho to describe social-ecological conditions that support and degrade their well-being. Using grounded theory methodology, we analyzed semi-structured interviews to discover meanings of well-being and to understand how people experience changes to their quality of life in an arid rangelands context. Our findings support previous research that suggests well-being is experienced at both individual and community scales, with sense of well-being influenced by ecological, economic, and socio-cultural processes. Specifically, our findings illuminate the role of social interactions as processes that support agroecosystem conditions and functions to the benefit or detriment of human well-being and ecosystem health. Community is not just a geographic territory; it is a process of social interactions through which people build, improve, or damage relationships that support or degrade well-being. By integrating scholarship on social change processes, ecosystem services, and impacts to human well-being, we contribute an integrated framework with a comprehensive set of social-ecological concepts to be used as a common language and synthesis guide for agroecosystem researchers and practitioners. We discuss our findings in the context of the USDA Agricultural Research Service’s national network for Long-Term Agroecosystem Research (LTAR). The LTAR network is charged with identifying strategies for sustainable intensification that support agricultural productivity, environmental quality, and rural well-being. Our research sheds light on the functions of agroecosystem stakeholders and rural communities beyond their adoption (or not) of new technologies and management practices. Future assessments of environmental change and impacts must adequately address social processes that, alongside ecological processes, affect well-being for rural communities and landscapes.